Literacy and perceptions of aging: Evidence from the Dani in Papua. (January 2022) - Sorokowski, Piotr; Oleszkiewicz, Anna; Löckenhoff, Corinna E.; Kowal, Marta; Frackowiak, Tomasz; Malecki, W.P.
Abstract: It has been hypothesized that an increase in literacy within a society is associated with more negative perceptions of aging and older adults. The present study empirically tested this premise among the Dani in West Papua. Sixty-one Dani participants were asked to nominate two individuals within each of the following categories: (1) most respected, (2) best source of life advice, and (3) most satisfied with life. They also reported the age and gender of the nominees. Literacy was associated with nominating younger targets in the life advice and life satisfaction categories. These results add evidence that literacy is associated with perceptions of older adults. We conclude by discussing the scholarly and practical implications of these findings. Highlights: The first empirical study on the influence of literacy on aging perceptions among the Dani. One of the first empirical studies on the topic conducted in nonindustrialized societies. Literacy contributes to aging perceptions. Illiterate participants are more likely to turn to older people for life and problem solving advice. Illiterate participants are more likely to ascribe high life satisfaction to older people.